2010
DOI: 10.1159/000315393
|View full text |Cite
|
Sign up to set email alerts
|

Sera of Elderly Bullous Pemphigoid Patients with Associated Neurological Diseases Recognize Bullous Pemphigoid Antigens in the Human Brain

Abstract: Background: Bullous pemphigoid (BP) is an acquired autoimmune dermatosis that is often associated with various neurological diseases (ND) in the elderly. Previously, we reported that BP antigen 1 (BPAG1) of the mouse brain can be recognized by serum samples of BP patients with ND (BP+ND), indicating the possibility that BPAG1 could act as a shared autoantigen of the skin and brain. However, it is not known whether the serum of BP+ND patients could recognize BPAG1 in the human brain. Objectives: The aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 24 publications
6
57
0
6
Order By: Relevance
“…The skin and neurons are both derived from the ectoderm, and the same hemidesmosomal protein antigens involved in the pathogenesis of BP are also expressed in human neurons (9,10). With regard to BP antigen 1 (BP230), a majority (54.5%) of serum samples from patients with BP and neurologic disease recognized a 230-kDa protein of human brain extract (31). Another study also showed that both human skin and brain contain immunogenic BP230 in patients with neurologic disease and BP (32).…”
Section: Discussionmentioning
confidence: 99%
“…The skin and neurons are both derived from the ectoderm, and the same hemidesmosomal protein antigens involved in the pathogenesis of BP are also expressed in human neurons (9,10). With regard to BP antigen 1 (BP230), a majority (54.5%) of serum samples from patients with BP and neurologic disease recognized a 230-kDa protein of human brain extract (31). Another study also showed that both human skin and brain contain immunogenic BP230 in patients with neurologic disease and BP (32).…”
Section: Discussionmentioning
confidence: 99%
“…Another study recently found that patients with BP showed a 3.62-fold increased risk for neurological disease prior to the diagnosis of BP [33]. These observations are particularly intriguing since evidence has been provided indicating that BP180 and BP230 are expressed in the central nervous system [34,35,36] and mice with defects in the dystonin gene, encoding for various isoforms of BPAG1 (including the epithelial isoform BP230/BPAG1-e), develop dystonia and sensory nerve degeneration [33,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies indicate that neurologic disease is an independent risk factor for BP (Bastuji-Garin et al, 2011; Langan et al, 2011; Stinco et al, 2005). BP is most strongly associated with dementia and Parkinson’s disease (PD), where the incidence is 2–4 times the expected rates in these diseases (Chen et al, 2011; Taghipour et al, 2010; Yang et al, 2011). …”
Section: To the Editormentioning
confidence: 99%